2016
DOI: 10.5137/1019-5149.jtn.16488-15.1
|View full text |Cite
|
Sign up to set email alerts
|

Adult brainstem gliomas - retrospective analysis of 51 patients

Abstract: ABSTRACTthe specific pathology all BSG must be considered malignant because their localization itself is inoperable (23). These tumors are most often localized in pons, often with infiltration in other regions of the brainstem (16). They characteristically present with multiple cranial nerve deficits, ataxia and long tract dysfunction (5,6,10). The simplest classification of BSG is into two groups as focal and diffuse (4,8). More complex grading system defined subtypes of tumors of the brainstem, according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…However, a previous study of 51 adult BSG patients showed that low-grade tumor was associated with pontine involvement. 5 Our results are consistent with some previous reports that indicate intra-tumoral necrosis (due to elevated level of lactate metabolite in tumor tissue) is associated with higher-grade tumors and/or worse prognosis. 12,21 In 48 diffuse BSGs in adults, necrosis on MRI, histological grading, and duration of symptoms were determined as significant predictors for unfavorable outcome.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, a previous study of 51 adult BSG patients showed that low-grade tumor was associated with pontine involvement. 5 Our results are consistent with some previous reports that indicate intra-tumoral necrosis (due to elevated level of lactate metabolite in tumor tissue) is associated with higher-grade tumors and/or worse prognosis. 12,21 In 48 diffuse BSGs in adults, necrosis on MRI, histological grading, and duration of symptoms were determined as significant predictors for unfavorable outcome.…”
Section: Discussionsupporting
confidence: 93%
“…However, a previous study of 51 adult BSG patients showed that low-grade tumor was associated with pontine involvement. 5…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And in adult HGBSG group, there were no difference between GTR and non-GTR group (P=0.67). Most clinical studies for adult patients with BSG included few patients treated with surgical resection (range from 0-14%) ( 21 , 22 , 31 ). A cohort with 16 consecutive adult patients treated with surgical resection, 2 of which achieved GTR, concluded that the surgical resection was of questionable benefits for adult patients ( 32 ).…”
Section: Discussionmentioning
confidence: 99%